Globalization of the steel industry - Hwang, Myung Hak (KDI School, 2000)
Steel is the vital and basic engineering material, underpinning all industrial development. Today consumption of steel is running at around 750 million tonnes a year, and world demand for steel is likely to grow for the foreseeable future. While steel is sold across international markets, it is primarily produced and supplied by national rather than global companies. The globalization of the steel producers is realized by way of the following processes: the progression of steel industry ownership from the state to the private sector, intra-regional alliances and consolidation, joint ventures with foreign partners, and finally full globalization. In this thesis, POSCO will be reviewed as a successful case of globalization. The successful companies in the future are likely to be embracing new technologies, be internationally cost competitive, and financially focused. They are also likely to have a network of strategic partners and joint ventures, with a much greater flexibility than has been exhibited by companies in the past.
Thesis(Master) --KDI School:Master of Business Administration,2000